Utilizing WhatsApp for Mutaba’ah during the Covid-19 Pandemic: Experiences of Ruquu Community Members in Bandung - Moch Fakhruroji; Nunung Nurhasanah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
The purpose of this study is to describe the mutaba'ah Al-Quran program through WhatsApp group interactions provided by the Ruquu Community in Bandung. The study focuses on the perceptions and experiences of these community members' involvement in the mutaba'ah program by employing a phenomenological method that depends on in-depth online and offline interviews with the community's founder as well as four purposefully selected community members. It can be argued that although it is something new, the mutaba'ah program through WhatsApp is a simple and voluntary process but has a positive impact on community members. This is due in part to the simplicity of the WhatsApp features. Furthermore, those who take part in the mutaba'ah program are highly motivated to study the Quran, despite the fact that some of them are still hindered by technological issues such as time availability and constraints related to limited internet connection at particular times.